2020
DOI: 10.5664/jcsm.8392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep-disordered breathing in opioid users with chronic pain: a systematic review and meta-analysis

Abstract: Study Objectives: Opioids have been reported to increase the risk for sleep-disordered breathing (SDB) in patients with noncancer chronic pain on opioid therapy. This study aims to determine the pooled prevalence of SDB in opioid users with chronic pain and compare it with patients with pain:no opioids and no pain:no opioids. Methods: A literature search of PubMed, Medline, Embase, and Cochrane Central Register of Controlled Trials was conducted. We included all observational studies that reported the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“… 17 , 146 , 147 Studies included in two systematic reviews demonstrated high prevalence of SDB and central sleep apnea (CSA) in patients using opioids for chronic pain, ranging from 75% to 91%, and 18% to 33%, respectively. 18 , 146 The risk of CSA was demonstrated to be higher in patients with lower body mass, when the dose of oral opioid ≥200 MEDD and opioids were combined with benzodiazepines or other CNS depressant agents. 17 , 146 , 148 Significant sleep disturbances were also demonstrated in an observational investigation in patients with advanced cancer (84%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 146 , 147 Studies included in two systematic reviews demonstrated high prevalence of SDB and central sleep apnea (CSA) in patients using opioids for chronic pain, ranging from 75% to 91%, and 18% to 33%, respectively. 18 , 146 The risk of CSA was demonstrated to be higher in patients with lower body mass, when the dose of oral opioid ≥200 MEDD and opioids were combined with benzodiazepines or other CNS depressant agents. 17 , 146 , 148 Significant sleep disturbances were also demonstrated in an observational investigation in patients with advanced cancer (84%).…”
Section: Resultsmentioning
confidence: 99%
“…Opioids have significant effects on the endocrine, immune, cardiovascular, respiratory, gastrointestinal and neural systems. [10][11][12][13][14][15][16][17][18][19][20] They increase the risk of fractures, infections, cardiovascular complications (including myocardial infarction), sleep disturbances and sleep-disordered breathing, bowel dysfunction, overdose and mortality due to opioid overdose or other causes. [15][16][17][18][21][22][23][24][25][26][27] Opioids may potentially affect cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…1. Although the study of Mubashir et al 11 13 whereas plant gain (efficiency of CO 2 excretion) may be increased. 14 Patients with chronic pain may be sedentary, contributing to increased body weight, and opioids seem to have vasodilatory properties that could contribute to fluid accumulation and rostral shifts.…”
mentioning
confidence: 95%
“…In this issue of the Journal of Clinical Sleep Medicine, Mubashir et al 11 report the results of a systematic review and meta-analysis of the prevalence of SDB among those using opioids for chronic pain. Their findings were based on 9 studies, in which they found an estimated prevalence of SDB of 91% among opioid users in sleep clinics and 63% in pain clinics, although the overall prevalence of SDB did not differ from those not using opioids.…”
mentioning
confidence: 99%
“…[24][25][26][27][28] Additionally, systematic reviews point to issues of tolerability, 29 and adverse effects including, but not limited to, constipation, 30 cognitive dysfunction, 31 endocrinopathy, 32 mood disturbance, 33 and sleep apnea. 34 Although some studies have attempted to demonstrate a causative relationship between opioid use and substance use disorders in chronic pain patients, variance in definitions and a prevalence of methodologically flawed studies based upon investigator bias make such a conclusion tenuous.…”
mentioning
confidence: 99%